Ghosts of the Haciendas: Memory, Architecture, and the Architecture of Memory in the Post-Hacienda Era of Southern Coastal Peru. - Weaver, Brendan J. M. (Ethnohistory, 2020)
The implementation of the Velasco administration's agrarian reforms in the 1970s transformed Peru's rural landscape and the ways in which communities relate to the physical reminders of the time of the haciendas. Community engagement during recent archaeological research at colonial Jesuit wine haciendas in Nasca's Ingenio Valley has revealed narratives that link historical memory on the former estates to fantastical imagery of ghosts, treasure, and mysterious tunnels, which simultaneously reference multiple attitudes related to a difficult past. This article ethnographically explores local engagement with hacienda architecture and memories of the hacienda period, which formulate a set of coexisting complex historical narratives indexing the modern communities' diversely experienced relationship to multiple historical events stretching into the deep colonial past, simultaneously expressing associated trauma, loss, and hope.